Ilmu Komunikasi Islam Dalam Perspektif Filsafat Ilmu - Basit, Abdu (Jurnal Komunikasi Islam, 2015)
Science Islamization movement has been penetrated into various of scientific disciplines, part of communication science. This science outward from West society traditions that it is separate between religion and science. The Separation implies for the formulation communication science and its aplication in living society that far from the divine teachings. In this context, islamization of communication science is urgent to researched. The problem of the studies whether is islamization of science just to labelling islam to communication science or is islam to provides new paradigm in developed communication science. Furthermore, how the da’wa science is?, is the islamization of communication science does not problematic with da’wa scientific? Da’wa science synonymous with islamic communication science, isn’t it? The prominent focus of this paper going to analyze islamization of communication science in the perspective of the philosophy of science, so that to results islamic communication science. The study onontology, epistemology, and axiology of islamic communication science are significant substance that will discuss in this paper.